2013
DOI: 10.1186/1471-230x-13-77
|View full text |Cite
|
Sign up to set email alerts
|

Age-of-onset-dependent influence of NOD2 gene variants on disease behaviour and treatment in Crohn’s disease

Abstract: BackgroundInfluence of genetic variants in the NOD2 gene may play a more important role in disease activity, behaviour and treatment of pediatric- than adult-onset Crohn’s disease (CD).Methods85 pediatric- and 117 adult-onset CD patients were tested for the three main NOD2 CD-associated variants (p.R702W, p.G908R and p.10007fs) and clinical data of at least two years of follow-up were compared regarding disease behaviour and activity, response to therapy and bone mineral density (BMD).ResultsChronic active and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…In our cohort 52% of patients carried at least one NOD2 risk allele, which is slightly higher compared to frequencies of 41-46% reported from other European cohorts. [25][26][27][28] Regional or ethnical differences, spectrum of CD patients at our centre or the relatively small Aliment Pharmacol Ther 2014; 39: 1398-1407number of patients may contribute to the difference. We found that children carrying at least one of the common two missense mutations in the NOD2 gene, R702W and G908R, have a detrimental 1 year outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort 52% of patients carried at least one NOD2 risk allele, which is slightly higher compared to frequencies of 41-46% reported from other European cohorts. [25][26][27][28] Regional or ethnical differences, spectrum of CD patients at our centre or the relatively small Aliment Pharmacol Ther 2014; 39: 1398-1407number of patients may contribute to the difference. We found that children carrying at least one of the common two missense mutations in the NOD2 gene, R702W and G908R, have a detrimental 1 year outcome.…”
Section: Discussionmentioning
confidence: 99%
“…28,58,79 Concern regarding 'Overall applicability' was rated as 'low' or 'unclear', except for five studies. 30,46,60,67,73 ROB and applicability for individual studies are presented in Box 1 and Figures 3-5.…”
Section: Discussionmentioning
confidence: 99%
“…The studies that were rated as having a high concern were four studies with composite outcomes defined in a slightly non-standard way and one study that enrolled Indian patients who had received antituberculous therapy only. 33 Aldhous 2007 34 Annese 2005 36 Beaugerie 2006 18 Brant 2003 37 Charpentier 2014 39 Chatzicostas 2006 40 Chen 2015 41 Choung 2016 42 Cleynen 2013 43 Goel 2013 46 Gupta 2006 47 Henckaerts 2009 48 Israeli 2014 25 Jauregui-Amezaga 2015 49 Laghi 2005 54 Lakatos 2009 56 Law 2013 57 Loly 2008 20 Louis 2003 26 Lovasz 2013 27 Lunney 2015 58 Malmborg 2015 59 Mazor 2011 60 Moon 2014 61 Nasir 2013 62 Nasir 2013 63 Nunes 2013 64 Odes 2001 65 Oriuchi 2003 67 Pandey 2015 68 Papi 2005 69 Park 2013 70 Pigneur 2010 71 Pittet 2013 28 Polito 1996 72 Posovszky 2013 73 Renda 2008 75 Romberg-Camps 2009 77 Ryan 2013 78 Sabate 2008 79 Sands 2003 80 Savoye 2012 81 Schaefer 2010 …”
Section: Overallmentioning
confidence: 99%
See 2 more Smart Citations